Co-evolutionary scenarios of intensification and privatization of resource use in rural communities of south-western Niger - Rovere, R. La; Hiernaux, Pierre H.Y.; Keulen, H. van; Schiere, J.B.; Szonyi, J.A. (Elsevier, 2005)
Agricultural production in the semi-arid agro-ecosystems of the Sahel centres on cereal staple crops and pastoralism with increasing crop-livestock integration. Animals mobilize soil fertility through manure production, graze crop by-products, and transfer nutrients from distant pastures to cropped areas. Yet in these systems various interacting factors, i.e. climate variability, poor soil fertility, poverty, and institutional constraints limit the capacity of agriculture to keep pace with the growing needs of an increasing human population. The major trends associated with population growth are (1) increasing area cropped at the expense of rangelands; (2) reduced availability of and access to good quality grazing resources, and (3) seasonal migration of labourers and transhumance of herds. These trends lead to co-evolution of farming systems towards increased privatisation of resource use. This study examines the implications of the development processes where farming systems co-evolve with their surroundings. It explores the impact of integrated management of livestock and crops in rural communities on both the livelihoods of differently endowed farms, and on the agro-ecosystem. Different scenarios explored the co-evolution of three sites situated in Western Niger with their environment. The sites differ in relative area cropped. The scenarios simulate the different future outcomes for varying socio-economic and biophysical criteria with either current or more intensive management.Explorative bio-economic models are used to compare a range of farm, livelihood and ecological indicators, and to reveal social and ecological trade-offs. If current agro-ecosystems and their environments co-evolve towards increased privatisation of grazing resources, then soil fertility is likely to deteriorate on the lands managed by the agro-pastoral groups. Soil fertility may improve on lands managed by the livestock-scarce farmers settled in villages, at the cost of declining farm incomes. The agro-pastoral groups are likely to resort to more distant pastures for feed. The village-based, livestock-endowed farms will resort to feeding on on-farm crop residues. Intensification, though associated with relative decreases in real incomes, will enhance food security in these new systems, except for the poorer settled farmers.